THE ROLE OF ECONOMIC EFFICIENCY AND BUSINESS STRATEGY TO ACHIEVE COMPETITIVE ADVANTAGE: Received: 25th September 2023; Revised: 09th October 2023, 02nd November 2023; Accepted: 30th November 2023 - Hidayat Abdullah, Edwin (PEOPLE: International Journal of Social Sciences, 2024)
An among company base on the organizational environments could lead conducts within an implementing economy of scale and the level of efficiency in identifying the number and variety of products and services that produce business can be profitable for the long term, to achieve competitive advantage in the industry. An asymmetric situation-based approach based on Agency Theory describes corporate business governance in which the company owner as a principal hires agent (company managers with various functional levels) to run the business of operating the organization in a complex industry. Meanwhile, analysis based on strategic choice theory pays attention; the relationship between managers of different functional levels and options, the constantly shifting market dynamics with the latest technological advances and innovations that continue to be made between business competitors, and the level of relationship between managers and the market are dynamic. For this reason, the author will develop a new concept of business strengthening that has the role of Economics, Efficiency, and Business Strategy to achieve Competitive Advantage in Companies in Industry in Indonesia with an approach based on Agency Theory and Strategic Choice Theory.